دوافع ممارسة الأنشطة الرياضية لدى طلبة جامعة بيرزيت - الطاهر، علي (جامعة النجاح الوطنية, 2007)
هدفت هذه الدراسة للتعرف على دوافع ممارسة الأنشطة الرياضية لدى طلبة جامعة بيرزيت، إضافة الى تحديد الفروق في درجة دوافع الطلبة تبعا لمتغيري الجنس ونوع الكلية. ولتحقيق ذلك أجريت الدراسة على عينة عشوائية قوامها (394) طالبا وطالبة، حيث طبق عليها مقياس فردريك وريان (Fredrick & Ryan 1993) لقياس الدوافع، وأظهرت نتائج الدراسة أن درجة الدوافع لدى الطلبة كانت كبيرة حيث وصلت النسبة المئوية للاستجابة (73.6%)، وأن دوافع مجال اللياقة البدنية جاءت في المرتبة الأولى بنسبة مئوية وصلت الى (82.2%)، إضافة إلى وجود تفاعل بين متغيري الجنس ونوع الكلية والتفاعل بينهما، ولم تكن الفروق دالة إحصائيا في الدرجة الكلية للدوافع تبعا لمتغيري الجنس ونوع الكلية والتفاعل بينهما، وكان هناك تفاعل فقط في مجالي المظهر العام واللياقة البدنية. وأوصى الباحث بعدة توصيات من أهمها، زيادة اهتمام المسؤولين في عمادة شؤون الطلبة بالأنشطة الرياضية التي تنمي العلاقات الاجتماعية. This study aims at identifying the degree of motivation by Birzeit University students towards practicing sports activities and identifying the discrepancy in the students’ level of motivation according to gender and college variables. The sample included 394 female and male students. It was conducted using Fredrick & Ryan 1993 scale that consists of thirty items divided into five domains: interest and enjoyment, competition, appearance, physical fitness, social relations domain. The data was analyzed using percentages, means, and the Two-Way ANOVA. The results showed that students practicing in terms of priority came as follows respectively: physical fitness, (82.2%), appearance (74.2%), enjoyment (72.8%), competition (71.8%) and social relations (66.6%). The study also indicated that there was no significant statistical difference in the student’s motivation due to gender and college variables. Moreover, there was no interaction between them except in the domain of appearance and physical fitness. The study drew the attention of the students Affairs Deanery to the importance of sports activities that develop social relationships.
729397 36128 763200
Keywords: الفروق الفردية -- النشاط الرياضي -- التعليم الجامعي -- الجامعات والكليات -- جامعة بيرزيت -- طلاب الجامعات -- الذكور -- الإناث -- اللياقة البدنية -- العلاقات الاجتماعية -- الدافعية -- التوتر -- السلوك -- علم النفس التربوي